A randomized trial of ketorolac and metoclopramide for migraine in the emergency department. Issue 6 (7th June 2022) - Richer, Lawrence P.; Ali, Samina; Johnson, David W.; Rosychuk, Rhonda J.; Newton, Amanda S.; Rowe, Brian H.
Abstract: Objective: The objective of this study was to assess the efficacy and safety of a common monotherapy (intravenous [iv] metoclopramide) compared to a combination strategy (adding iv ketorolac to metoclopramide) in children presenting for acute treatment of migraine headache in the emergency department (ED). Methods: Children aged 5–17 years presenting for acute treatment of migraine headache at two pediatric EDs were enrolled in a double‐blind randomized controlled trial. Children were randomly assigned to receive iv metoclopramide 0.2 mg/kg) and placebo or iv metoclopramide (0.2 mg/kg) and ketorolac (0.5 mg/kg). The primary outcome was a mean change in pain from baseline to 120 min via a 100 mm Visual Analog Scale (VAS). Follow‐up was conducted 24‐h after discharge. Results: Fifty‐three children were randomized and included in the analysis (monotherapy group [metoclopramide + placebo], n = 27; and ketorolac group [metoclopramide + ketorolac], n = 26); mean age was 12.9 ± 2.7 years and baseline pain severity on VAS was 67.3 ± 2.7 mm. The mean change in pain intensity at 120 min was −44 mm (SD: 24; 95% confidence interval [CI]: 32–57) for the monotherapy group and −36 mm (SD: 24; 95% CI: 23–49) for the ketorolac group, with a mean difference between groups of 8 mm (95% CI: −9–25; p = 0.360). Seventeen percent of the children (9/53; 95% CI: 7–27%) were pain‐free at discharge. There was no difference in headache recurrence or adverse events between groups. Conclusions: The approach of combining iv metoclopramide with ketorolac failed to improve pain scores in children presenting for acute treatment of migraine headache in the ED compared to metoclopramide monotherapy. Most patients were discharged with residual pain. Further comparative studies are needed to test alternative ED treatments for migraine in children or adolescents.